Determination of carbohydrates contents in pruned and unpruned almond cultivars - Ikinci A.; Küden A.; Ak B.E. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
The effect of pruning on carbohydrates content of ‘Nonpareil’ and ‘101-9’ almond cultivars was investigated. In this experiment, summer and winter (dormant) pruning was applied at different times. A randomized complete block design with 3 single tree replications for each pruning treatment was used for each cultivar. The following pruning treatments were each applied to one tree in each block: (a) unpruned (control); (b) pruned in June; (c) pruned in July; (d) pruned in August; (e) pruned in September; and (f) only winter pruning (WP). Water-soluble reducing sugars (SRS), total sugars, hydrolyzed starch and sucrose contents were analyzed. The samples were taken after pruning. Dormant and summer pruning treatments had different effects on carbohydrate contents of almond. Generally, control and dormant pruned trees had higher carbohydrate content than summer pruned trees. Earlier summer pruning (June or July) lowered carbohydrate content more than late summer pruning.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)